Involving Older Adults During COVID-19 Restrictions in Developing an Ecosystem Supporting Active Aging: Overview of Alternative Elicitation Methods and Common Requirements From Five European Countries - Mooses, Kerli; Camacho, Mariana; Cavallo, Filippo; Burnard, Michael David; Dantas, Carina; D’Onofrio, Grazia; Fernandes, Adriano; Fiorini, Laura; Gama, Ana; Perandrés Gómez, Ana; Gonzalez, Lucia; Guardado, Diana; et al. (Frontiers in Psychology, 2022)
Background: Information and communication technology solutions have the potential to support active and healthy aging, improve monitoring and treatment outcomes. To make such solutions acceptable, all stakeholders must be involved in the requirements elicitation process. Due to the COVID-19 situation alternative approaches to commonly used face-to-face methods must often be used. One aim of current article is to share a unique experience from the Pharaon project where due to the COVID-19 outbreak alternative elicitation methods were used. In addition, an overview of common functional, quality and emotional goals identified by six pilot sites are presented to complement the knowledge about the needs of older adults. Methods: Originally planned face-to-face co-creation seminars were impossible to carry and all pilot sites chose alternative requirements elicitation methods that were most suitable in their situation. The elicited requirements were presented in the form of goal models. In one summary goal model we provide an overview of common functional, quality and emotional goals. Results: Different elicitation methods were combined based on the digital literacy of the target group and their access to digital tools. Methods applied without digital technologies were phone interviews, reviews of literature and previous projects, while by means of digital technologies online interviews, online questionnaires, and (semi-)virtual co-creation seminars were conducted. The combination of the methods allowed to involve all planned stakeholders. Virtual and semi-virtual co-creation seminars created collaborative environment comparable to face-to-face situations, while online participation helped to save the time of the participants. The most prevalent functional goals elicited were “Monitor health”, “Receive advice”, “Receive information”. “Easy to use / comfortable”, “personalized / tailored”, “automatic / smart” were identified as most prevalent quality goals. Most frequently occurring emotional goals were “involved”, “empowered”, and “informed”. Conclusion: There are alternative methods to face-to-face co-creation seminars which effectively involve older adults and other stakeholders in the requirements elicitation process. Despite the used elicitation method, the requirements can be easily transformed into goal models to present the results in a uniform way. The common requirements across different pilots provided a strong foundation for representing detailed requirements and input for further software development processes.